METODE MODIFIKASI NEWTON √ DENGAN ORDE KONVERGENSI 1 + 2 - Lely Jusnita; Supriadi Putra; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss the modification of Newton’s method, which is a Predictor and Corrector method, to solve a nonlinear equation. Using a series based on the equation √ error of the method, we show that the order of convergence of the method is 1 + 2 and for each iteration, it requires two function evaluations, so the efficiency index of the method is 2.4142. To see the advantages of the proposed method, we compare the method with some known iterative methods using four test functions by varying an initial guess.